IMPACT OF DIGITAL RESOURCES AVAILABILITY AND UTILIZATION ON THE SERVICE DELIVERY OF ACADEMIC STAFF IN UNIVERSITIES IN CROSS RIVER STATE, NIGERIA (Journal of Association of Educational Management and Policy Practitioners, 2025)
The availability and utilization of digital resources are crucial for enhancing the service delivery of academic staff in universities. Premised on this, a study was conducted to examine the impact of Digital Resources Availability and Utilization on the Service Delivery of Academic Staff in Universities in Cross River State. Two research hypotheses guided the study. Descriptive survey research design was adopted. The population of the study was all 2,795 academic staff (lecturers) from two public universities in Cross River State, University of Calabar (UNICAL) and University of Cross River State (UNICROSS) and the study sample size was 280 (10%) male and female lecturers selected through stratified and simple random techniques from both universities. Data were collected using a questionnaire entitled: "Digital Resources Availability and Utilization” and “Service Delivery of Academic Staff Questionnaire (DRAVSDAS). The scale was structured into three sections. Responses to Section A were used to determine the demographic characteristics of the respondents. Section B and C provided information on Digital Resources Availability and Utilization and Service Delivery of Academic Staff. The validity of the instrument was determined by three experts. Two from Test Measure and Evaluation, and one from Educational Management, University of Calabar. With the use of the Cronbach alpha reliability method, the reliability of the instrument was determined and the coefficient estimate were .82, .86, and .87, respectively. To collect data for the study, all the researchers visited the universities with copies of the questionnaire. They hypotheses were tested at .05 level of significance, using Simple Linear Regression and Multiple Regression analyses of statistical package for social science (SPSS) version 27 for data analysis. The result revealed that digital resources availability and utilization has a statistically significant, positive impact on the service delivery of academic staff in public universities in Cross River State, Nigeria. The study concluded that availability and utilization of digital resources significantly enhance the service delivery of academic staff in universities, leading to improved teaching, research, and administrative efficiency. It was recommended among others the investing in robust digital infrastructure, such as high-speed internet, up-to-date software, and reliable hardware, is crucial to improve the efficiency and effectiveness of academic staff's service delivery.